Етапи та тенденції розвитку іншомовної освіти в контексті підготовки майбутніх учителів - Оніщук, І. І.; Шапошнікова, Олена Павлівна; Шальов, А. С.; П'ясецька, Н. А.; Тонконог, Н. І.; Зелінська, Т. М.; Бабаджанян, Вікторія Володимирівна; Шпильова, М. О. (Національний педагогічний університет ім. М. П. Драгоманова, 2020)
У науковому дискурсі загальновизнано, що існуюча система іншомовної освіти є результатом її тривалого історичного розвитку, тому аналіз і узагальнення історичного досвіду даної галузі є необхідним у період модернізації сучасної гуманітарної освіти в Україні. Аналіз історичних, соціальних, культурних та педагогічних умов і чинників, що призвели до змін мети, завдань, змісту іншомовної освіти в Україні, дозволив визначити три етапи розвитку іншомовної освіти у контексті підготовки майбутніх учителів фізичної культури у педагогічних університетах України в період з середини ХХ до початку ХХІ століття. Перший етап (1950 – 1960) – етап формування загальнонаукового інтересу до феномену іншомовної освіти. Другий етап (1970 – 1980) – іншомовна освіта в умовах реформування вищої школи. Третій етап (1990 – 2018) – етап сталого розвитку іншомовної освіти в умовах інтеграції в європейський освітній простір. Історіографічний аналіз дозволив визначити міждисциплінарну сутність іншомовної освіти, яка полягає в тому, що: вивчення будь-якої нерідної мови має супроводжуватися вивченням культури народу, котрий розвиває вміння розуміти світову культуру в цілому, формує здатність орієнтуватися в сучасному полікультурному й інформаційному суспільстві.

It is generally accepted in the scientific discourse that the existing system of foreign language education is the result of its long historical development, therefore, the analysis and generalization of the historical experience of this industry is necessary during the modernization of modern humanitarian education in Ukraine. The analysis of historical, social, cultural and, pedagogical conditions and factors that led to changes in the purpose, tasks and, the content of foreign-language education in Ukraine made it possible to determine three stages of the development of foreign language education in the context of future physical education teachers‟ preparation at pedagogical universities in Ukraine from the middle of the ХХ to the beginning of the ХХІ century. The first stage (1950-1960) is the stage of forming the general scientific interest in the phenomenon of foreignlanguage education. The second stage (1970-1980) is foreign language education in the conditions of higher education reform. The third stage (1990-2018) is the stage of sustainable development of foreign language education in the conditions of integration into the European educational space. The historiographic analysis made it possible to determine the interdisciplinary essence of foreign language education, which is that: learning of any non-native language has to be accompanied by studying the culture of the people, which develops the ability to understand world culture as a whole, forms the ability to navigate in a modern multicultural and information society
Stages and trends in the development of foreign language education in the context of future teachers' training
Keywords: історичний розвиток; вчитель фізичної культури; гуманітарна освіта; педагогічні умови і чинники; історіографічний аналіз; культура народу; historical development; physical education teacher; humanitarian education; pedagogical conditions and factors; historiographic analysis; the culture of the people